Effects of Cotton–Peanut Intercropping Patterns on Cotton Yield Formation and Economic Benefits - Wang, Guifeng; Wang, Depeng; Zhou, Xiaoyan; Shah, Saud; Wang, Lichen; Ahmed, Mukhtar; Sayyed, R. Z.; Fahad, Shah (Frontiers in Sustainable Food Systems, 2022)
Intercropping has been widely adopted by farmers for it often enhances crop productivity and economic returns. However, In order to improve the comprehensive production benefits of agricultural cultivation and increase the economic benefits of cotton in Northwest Shandong Province, a set of green, ecological and efficient intercropping mode suitable forNorthwest Shandong Province was preliminarily formed. A two-year intercropping experiment was conducted in Xiajin and Dongping Counties in Shandong Province’s, with six alternative intercropping patterns were proposed. After analyzing the experimental data, the traditional cotton peanut intercropping method is not mechanized, a new intercropping mode has been proposed: four rows of cotton and six rows of peanut .we selected the appropriate intercropping mode for Xiajin and Dongping Counties. The production efficiency of 4:4 cotton intercropping in Peanut Ridge was the best in Dongping and Xiajin County, which was 28-123% % higher than that of monoculture, This planting pattern is suitable for demonstration and promotion in the two counties and even in the traditional cotton area of old Yellow River in Northwest Shandong.